The Sport Education Model as a training possibility: an experience in initial training in Physical Education (Research, Society and Development, 2020)
Objective: Analyze the perception of students from an undergraduate course in Physical Education of a public university in Brazil on the implementation of the Sport Education Model (SEM) during the teaching and learning process in the scope of team sports. Methods: Based on a qualitative research of interventional nature, the results generated from the interviews, images from the practical activities and field journal – evaluated through a content analysis Results: Highlight that the use of SEM as a possibility for students to understand the teaching and learning process in the scope of team sports produced actions of cooperation and development of a sense of collective belonging during the classes. Conclusions: The process of intervention based on the SEM demonstrated to have contributed significantly to enlarge the learning experience of the students in the environment of team sports, thus promoting a reflection on the actions performed and greater independence during class.